Phylogeny, classification and species delimitation in the liverwort genus Odontoschisma (Cephaloziaceae). Issue 5 (1st October 2014) - Aranda, Silvia C.; Gradstein, S. Robbert; Patiño, Jairo; Laenen, Benjamin; Désamoré, Aurélie; Vanderpoorten, Alain
Abstract: A species‐level phylogeny of Odontoschisma (Jungermanniidae: Cephaloziaceae) was produced to revisit the infrageneric classification and delimit the species within the genus. New methods of species delimitation have been used to explicitly contrast taxonomic hypotheses and test the relevance of the morphological traits traditionally used in this group. The results confirm previous evidence suggesting that the circumscription of Odontoschisma needs to be enlarged to include Iwatsukia and Cladopodiella, and further indicate that a third genus, Anomoclada, is nested within it. Twenty‐three molecular entities were recognized based the results of generalized mixed Yule‐coalescent (GMYC) analyses. These entities partly conflicted with traditionally defined species that were shown to belong to different, not necessarily closely related entities, adding to the growing body of evidence calling for an extensive revision of species delimitations in taxa with reduced morphologies like leafy liverworts, using an integrative taxonomic approach. A fully revised classification of Odontoschisma into five sections, twenty species, and three subspecies is presented. While the species reported from Europe, Asia and North America were of polyphyletic origins, all Neotropical species were resolved as monophyletic, which could result from a combination of fast speciation rates and reduced dispersal in the Neotropics, and potential extinction in other areas, especially sub‐Saharan Africa.